Electrical Behaviour of Association Phenomena of Tetra aqua-1,10-phenanthroline Iron (II) Chloride in Methanol-Water Mixtures at Different Temperatures - Y.O. Hameed; F.A. Thanon; S.H. Abdul-Rahman (College of Education for Pure Sciences, 2008)
ABSTRACT The electrical behaviour of mixed ligand complex of Fe(II) in different percentage of binary mixture of methanol and water at different temperatures can give information about ion-ion and ion-solvent interaction in solution so the limiting molar conductance , KA the association constant and (R) the main distance between ions in solution as a results of those interaction can be calculated. Thermodynamics parameters (H, G, S) of the association processes and the coulombic forces which play an important role in the association process also have been studied, Walden product also calculated for solvent composition which indicate the tendency of the association of the ions in different percentages.